Contextual Effect of the Integrated Health Post and Social Capital on Completeness of Child Immunization in Pacitan, East Java - Puspita Mayangsari Prabowo; Setyo Sri Rahardjo; Eti Poncorini Pamungkasari (Journal of Maternal and Child Health, 2020)
Background: Around 2-3 million deaths each yearwere caused by diseases that could be pre